Professions and organizations: A European perspective. Issue 1 (February 2016) - Brock, David M.; Saks, Mike
Abstract: This article surveys the literature from two complementary traditions on understanding professions in organizations – namely, the sociological analysis of professions and the more managerialist organizational theory. Notwithstanding their strong North American roots, these strands are brought together to provide a blended European perspective on professions in organizations based on the now dominant and interrelated neo-Weberian and neo-institutionalist theories. Initially centering on North American roots, it is noted that the European literature deriving from this blended theoretical base has been mushrooming in recent years. The range of issues addressed by this research is highlighted with reference to a number of specific professional groups in Europe. We then focus on a cohesive case study on the professions and organizations in healthcare, to which so much attention has been given by researchers in this field.